EFFICIENT TREATMENT OF ATRIAL FIBRILLATION USING THREE-DIMENSIONAL ELECTRICAL POTENTIAL MODEL (2015)
A method for guiding electrophysiology (EP) intervention using a patient-specific electrophysiology model includes acquiring a medical image of a patient subject (S). Sparse EP signals are acquired over an anatomy using the medical image for guidance (S). The sparse EP signals are interpolated using a patient specific computational electrophysiology model and a three-dimensional model of EP dynamics is generated therefrom (S). A rendering of the three-dimensional model is displayed. Candidate intervention sites are received, effects on the EP dynamics resulting from intervention at the candidate intervention sites is simulated using the model, and a rendering of the model showing the simulated effects is displayed (S).